The Effect of Content Instruction in L2 on L1 Pragmatics - Kanik, Mehmet (Research in Language, 2011)
This study investigates whether content instruction in English has an impact on L1 pragmatics. In this study a discourse completion test with eight request situations in Turkish was given to three groups of Turkish students enrolled in undergraduate programs in a faculty of education in Turkey. One group of students received most of their education in English. The other two groups received their education in Turkish. An interesting finding is that the differences in the make-up of the situations were only observed in situations with high imposition. This shows that instruction in the foreign language has an impact on sociopragmatic interpretation in L1. Overall, the results reveal that instruction in foreign language has an impact on first language pragmatic use.